2001
DOI: 10.1007/pl00002030
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Standardization of EBT and MSCT Scanning

Abstract: The article summarizes guidelines for image acquisition and evaluation by EBT and describes guidelines and consensus reports that were issued concerning the clinical use of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Hemodynamically relevant stenoses also were detected with only 72.2% sensitivity. Four of the five missed stenoses were either located within small segments or were hidden by heavy calcifications: a possible explanation why our results were worse than those reported by other authors (Table 4) [18,28,29,30,31,32], who either concentrated on the proximal and medial coronary artery segments or excluded heavy calcified segments from evaluation; however, by combining calcium scoring and computerized coronary angiography sensitivity of MDCTA was augmented to 83% (Fig. 2).…”
Section: Discussioncontrasting
confidence: 80%
“…Hemodynamically relevant stenoses also were detected with only 72.2% sensitivity. Four of the five missed stenoses were either located within small segments or were hidden by heavy calcifications: a possible explanation why our results were worse than those reported by other authors (Table 4) [18,28,29,30,31,32], who either concentrated on the proximal and medial coronary artery segments or excluded heavy calcified segments from evaluation; however, by combining calcium scoring and computerized coronary angiography sensitivity of MDCTA was augmented to 83% (Fig. 2).…”
Section: Discussioncontrasting
confidence: 80%
“…The same generation scanner should be used Heart-rate (HR) should be acceptable Mass equivalent should be used for subsequent followup Exclude pericardial and/or mitral valve calcifi cation [Figure 4] The AHA Writing Group proposes that the following minimum requirements be met in scanning for CS: [33] 1. Use of an electron beam scanner or a 4-level (or greater)…”
Section: How Good Is the Reliability And Reproducibility Of Results O...mentioning
confidence: 99%
“…The International Consortium for the Standardization of Cardiac CT revealed that MSCT is an equal and potentially superior cardiac imaging modality compared to EBCT. [33] Increased temporal resolution and reduction in slice thickness improve CS results. In a two-year prospective study [34] of 1173 asymptomatic patients without documented CAD, CS was measured by EBCT and found to be predictive of CAD events.…”
mentioning
confidence: 99%